Altered running economy directly translates to altered distance-running performance - Hoogkamer, W.; Kipp, S.; Spiering, B. A.; Kram, R. (Medicine & Science in Sports & Exercise, 2016)
Purpose: Our goal was to quantify if small (1%-3%) changes in running economy quantitatively affect distance-running performance. Based on the linear relationship between metabolic rate and running velocity and on earlier observations that added shoe mass increases metabolic rate by ~1% per 100 g per shoe, we hypothesized that adding 100 and 300 g per shoe would slow 3000-m time-trial performance by 1% and 3%, respectively.